The Implementing of Using Wordwall as a Media to Improve The Students’ Vocabulary Achievement in New Normal Era - Riza Datul Amaliyah; Endang Mastuti Rahayu (Edu-Ling: Journal of English Education and Linguistics, 2023)
The objectives of this research were to improve vocabulary achievement by using Wordwall web-based application at the eleventh grade students of SMAN 1 KRIAN. Classroom action research was used as the research approach. This study's sample consisted of one class of 28 eleventh grade students. The data were gathered by using observation, tests and questionnaire and were analysed by descriptive statistic for vocabulary test scores and descriptive qualitative for the observation results and questionnaire. In accordance with the findings, only 21% of students passed the KKM during pre-cycle. Students' results improved in post-test I, with 71% passed the KKM. Students' scores improved in the post-test II, with 86% of students who completed the KKM. As many as 93% students gave positive opinion that said was fun and easier did exercieses in Wordwall. In conclusion, used Wordwall in learning can improve student’s vocabulary achievment.